Teknik Pemilihan Kontrasepsi Darurat oleh Akseptor KB selama Pandemi Covid-19 dalam Menjaga Kesehatan Reproduksi di Puskesmas Maccini - Ekayanti Hafidah Ahmad; Erna Kasim; Magdalena Limbong; Nor Auliana Sari4; Dimas Riyadil Amin (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The number of women of childbearing age in Indonesia is the largest number of WUS in Southeast Asia. However, Indonesia is the largest user of contraception. The Covid-19 outbreak also affects the use of contraception. This outbreak was declared a global health emergency, requiring restrictions on physical and social activities and contacts, up to large-scale quarantine. This causes major changes in the social structure, which usually changes activities outside the home to activities at home. Apart from that, the pandemic has also increased sexual contact, thereby allowing an increase in the number of pregnancies. So it is necessary to strengthen knowledge on the use of contraception. The aim of this activity is to assist PUS in choosing the type of contraception during the Covid-19 pandemic in maintaining reproductive health using counseling methods on contraceptive selection. This community service activity has been successfully implemented. WUS in the Maccini Health Center area of Makassar City have also received information about contraception, especially during the Covid-19 pandemic. Judging from the EFA response, this activity was welcomed and considered to have provided positive benefits during the pandemic.